Species profiles life histories and environmental requirements of coastal fishes and invertebrates (Pacific Northwest)--Pacific herring - Lassuy, Dennis R. (Washington, D.C U.S. Department of the Interior, 1989)
U.S. Fish Wildl. Serv. Biol. Rep 82(11.126)
Keywords: Invertebrates; Fishes; History; Pacific; Pacific herring--Pacific Nortwest